Profitabilitas dan efisiensi usahatani jagung (Kasus di Desa Kadipaten Kecamatan Kadipaten Kabupaten Tasikmalaya) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
The increase in demand of corn exceeds the increase in its production in Indonesia resulting on increasing rate of annual import. It opens the opportunity for farmers to increase production either through intensification or area expansion (extensification). A research conducted in Kadipaten Village, Kecamatan Kadipaten Kabupaten Tasikmalaya aimed to find out: (1) farmer's benefit from corn farming, (2) value of domestic cost ratio of corn farming, and (3) value changes of the domestic cost ratio of corn farming resulted from the changes of input costs, fertilizer and labor wages. A survey method was used on corn farming offarmer group of Wargi Saluyu in the Kadipaten Village. 28 sample farmers are taken randomly from 187 farmers. The data were then analyzed using Policy Analysis Matrix (PAM) by elaborating the domestic resource cost ratio (DRCR). The results.showed that: ( 1 )Corn farming carried out by farmer group of Wargi Saluyu in the Kadipaten Village, based both on market and social prices was beneficial. It was indicated with the benefit value greater than zero. The benefit from one hectare land area in one production period at the market price was Rp 682,433 or Rp 136 per kilogram and at social price was Rp 2,666,080 or Rp 532 per kilogram. (2)The domestic resource cost ratio was less than one, 0.46, it mean that one unit increase of value added needs 0.46 unit of domestic cost, and indicated that the corn farming run by the group farmer was efficient. (3)The changes of output prices, labor wages, and fertilizer cost by 15 percent showed that the corn farming had a high stability, indicated with the DRCR value remained less than one. The simultaneous decrease and increase of output prices, the increase of labor wages and fertilizer price by 15 percent suggested that the corn farming was economically efficient.